2018
DOI: 10.1038/s41598-018-32640-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon microscopy of Paneth cells in the small intestine of live mice

Abstract: Paneth cells are one of the principal epithelial cell types in the small intestine, located at the base of intestinal crypts. Paneth cells play key roles in intestinal host-microbe homeostasis via granule secretion, and their dysfunction is implicated in pathogenesis of several diseases including Crohn’s disease. Despite their physiological importance, study of Paneth cells has been hampered by the limited accessibility and lack of labeling methods. In this study, we developed a simple in vivo imaging method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Intravital imaging for the GI tract, liver, skin, and lymph node were done as previously described 53–57 and reviewed in ref. 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Intravital imaging for the GI tract, liver, skin, and lymph node were done as previously described 53–57 and reviewed in ref. 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Mock-infected cells served as negative controls. UEA-1 lectin was chosen as it can stain multiple intestinal cell types (e.g., entero-endocrine cells [24], colon adenocarcinoma cells [24], small intestinal epithelial cells [25], goblet cells [26], Paneth cells [27]) in different mammalian species. As anticipated, no viral staining was observed in mock-infected cells (Fig 3A).…”
Section: Va1 Shows Tropism For Multiple Cell Typesmentioning
confidence: 99%
“…[ 28 ] This influence of PC is mediated by such factors as Wnt‐ligands (Wnt3, Wnt6 and Wnt9b), Notch ligands (Dll‐1 and Dll‐4), as well as epidermal (EGF) and α‐transforming (TGF‐α) growth factors. [ 4,12–20,22–25,27,28,30–60 ] PC affect +LGR5‐cells predominantly through the Wnt signaling pathway. [ 14 ] Wnt proteins are membrane‐bound ligands that are necessary for cell development, migration, and polarization.…”
Section: Location Morphology and Function Of Paneth Cellsmentioning
confidence: 99%
“…[ 6 ] In addition, PC secrete Notch ligands on their membranes, such as Dll1 and Dll4, which bind the Notch receptors on intestinal stem cells, that leads to an increase in the number of stem cells. [ 2,4–20,22–25,27,28,30–59,61–65 ] Recent studies have shown that there is also a metabolic interdependence between PC and stem cells. [ 7 ] Therefore, remarkably, stem cells receive signals that regulate their activity from their descendants—PC.…”
Section: Location Morphology and Function Of Paneth Cellsmentioning
confidence: 99%
See 1 more Smart Citation